If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -5sqrt(x) + 6 = 0 Multiply qrst * x x + -5qrstx + 6 = 0 Reorder the terms: 6 + -5qrstx + x = 0 Solving 6 + -5qrstx + x = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -5qrstx + -6 + x = 0 + -6 Reorder the terms: 6 + -6 + -5qrstx + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5qrstx + x = 0 + -6 -5qrstx + x = 0 + -6 Combine like terms: 0 + -6 = -6 -5qrstx + x = -6 Add '-1x' to each side of the equation. -5qrstx + x + -1x = -6 + -1x Combine like terms: x + -1x = 0 -5qrstx + 0 = -6 + -1x -5qrstx = -6 + -1x Divide each side by '-5rstx'. q = 1.2r-1s-1t-1x-1 + 0.2r-1s-1t-1 Simplifying q = 1.2r-1s-1t-1x-1 + 0.2r-1s-1t-1 Reorder the terms: q = 0.2r-1s-1t-1 + 1.2r-1s-1t-1x-1
| 5y-9=4y+6 | | y=5-3(-2) | | 2.25x=15.75 | | .60x+.25=.35x-4 | | c=4.95p+32.50 | | x^2-36x+324=1 | | 2(4-0.3b)=6.5 | | 8x-7=x(A+2B)+A-3B | | .25b+.40b-5=-3 | | 4.9(t)+10(t)-5=0 | | 8x+2x-10=100 | | [(x)(x)]-x=2 | | 25h=-15h-80 | | 3/4+x-2=3/5 | | -x+7(x-5)=-32+7x | | 4x-18=10x+8 | | y=5x-2-7 | | 25h=-1h-80 | | [k-5]=4 | | 2x-10=4+x | | 4.9t^2-5t=-12 | | 5.5x+26=5x-10 | | 6+35=21x+30 | | 2a-11=-8a+30 | | x+12=-46 | | 2n*3=48 | | 50x+680=20x+950 | | 3c-5=2c+6 | | 5x^2+27x=18 | | 24.54x+9.50=105 | | 4x+5(2x-11)=71 | | x+5*3=39 |